MANAJEMEN SDM: PERAN ORGANISASI PENDIDIK DALAM MENINGKATKAN PROFESIONALISME GURU DI SD GLOBAL GARUDA NUSANTARA ISLAMIC CENTRE - Mustofa, Maulana; Elda Yudistari; Asy’ari, Hasyim; Ratnaningsih, Sita (STIT PRINGSEWU, 2024)
This study examines the role of educational organizations, specifically MGMP and GPAI, in enhancing teacher professionalism in Bogor, West Java. Qualitative research methods, including observations, interviews, and document analysis, were employed to investigate the activities, collaboration, and impact of these organizations. The findings indicate that MGMP and GPAI play a crucial role in promoting collaboration among teachers, sharing best practices, and improving teaching methods and curriculum development. The support from school management and local government is essential for the success of these organizations. Implementing relevant and effective programs has resulted in improved teaching quality and better student learning outcomes. The study emphasizes the importance of sustaining and reinforcing the involvement of MGMP and GPAI in Bogor's education system. Recommendations include increasing teacher participation, developing comprehensive professional development programs, fostering collaboration among educational institutions, local government, and the community, and exploring additional factors influencing teacher professionalism. Future research should encompass a broader geographical area and consider variables like motivation, job satisfaction, and leadership within educational organizations. Strengthening teacher professionalism through collaboration and organizational support not only benefits teachers and students directly but also contributes to the overall development of education in Bogor, West Java.